2006
DOI: 10.1111/j.1467-9906.2006.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

What’s the ’Hood Got to Do with It? Parental Perceptions about How Neighborhood Mechanisms Affect Their Children

Abstract: During the past decade, a rapidly expanding body of empirical research has emerged that statistically links disadvantaged neighborhood environments with social and economic outcomes of low-income, minority children. Nonetheless, the mechanisms by which neighborhoods putatively affect children remain poorly understood. This article examines the perceptions of low-income parents regarding how their neighborhood might affect their children. We examine quantitative and qualitative data gathered from phone intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 62 publications
1
74
1
3
Order By: Relevance
“…However, there is less agreement about the mechanisms behind such contextual effects (Galster, 2012;Galster and Santiago, 2006). Different mediating processes discussed among researchers include social control, collective socialization, social capital, and institutional characteristics, see Ainsworth (2002) andGalster (2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is less agreement about the mechanisms behind such contextual effects (Galster, 2012;Galster and Santiago, 2006). Different mediating processes discussed among researchers include social control, collective socialization, social capital, and institutional characteristics, see Ainsworth (2002) andGalster (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such institutional mechanisms are discussed by a number of authors (Ainsworth, 2002;Galster and Santiago, 2006;Sampson, Morenoff and Gannon-Rowley, 2002) and relate, for example, to the quality of institutions and the availability of institutions such as health centers, schools, universities, hospitals and job centers (for a discussion of school effects see e.g. (Brännström, 2008;Sellstrom and Bremberg, 2006;Sykes and Musterd, 2011;Östh, Andersson and Malmberg, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In de literatuur over de mechanismen van buurteffecten worden scholen verondersteld een van de lokale instellingen te zijn die bijdragen aan plaatsgebonden effecten (Sampson e.a., 2002;Galster & Santiago, 2006). Het is bekend dat kenmerken van scholen (bijvoorbeeld kwaliteit en effectiviteit) van plaats tot plaats verschillen.…”
Section: Onderzoeksresultaten: Segregatiestudiesunclassified
“…The decision of households to reside in a particular sector within a city could be due to socioeconomic status (de Palma et al, 2007;Zondag & Pieters, 2005;Weisbrod et al, 1980), administrative and central character (Andrew & Meen, 2006;Axhausen et al, 2004;, Sociocultural network and ethnic ties (Ozo, 1986;Owusu, 2004;Kapoor et al, 2004), environmental and neighbourhood attributes (Clarke et al, 2006;Galster & Santiago, 2006), etc. Urban residential location models (Alonso, 1964;Muth, 1969;Mills, 1967Mills, , 1972 indicate that the determinants of choice of residential location include income of the household, family size, population density, rent and cost of movement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other literature has shown that households may be attracted to a particular area because some neighbourhoods provide satisfaction or dissatisfaction due to the presence or absence of good quality schools, crime, noise, social interaction and community spirit (Parkes et al, 2002;Galster & Santiago, 2006). For example, in China households seeking for a home are willing to pay more for reputable sectors and for areas where the quality of neighbourhood with respect to security, accessibility and convenience is high (Wang & Li, 2006).…”
Section: Neighbourhood and Environmental Attractivenessmentioning
confidence: 99%